2018
DOI: 10.1016/j.trc.2017.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing battery electric vehicle feasibility from taxi travel patterns: The case study of New York City, USA

Abstract: Electric taxis have the potential to improve urban air quality and save driver's energy expenditure. Although battery electric vehicles (BEVs) have drawbacks such as the limited range and charging inconvenience, technological progress has been presenting promising potential for electric taxis. Many cities around the world including New York City, USA are taking initiatives to replace gasoline taxis with plug-in electric vehicles. This paper extracts ten variables from the trip data of the New York City yellow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 25 publications
2
51
0
2
Order By: Relevance
“…With battery capacities below 30 kWh, already 75% of the taxis could be electric and would lead to global cost reductions of 20%. For New York City, USA, Hu et al [18] state a need for more public chargers that would allow electrifying more than half of the taxi fleet with BEV. Deyang et al [19] use simulation to determine techno-economically optimal battery sizes for electric taxis based on taxi data from Shanghai, China.…”
Section: A Existing Literature and Scope Of This Studymentioning
confidence: 99%
“…With battery capacities below 30 kWh, already 75% of the taxis could be electric and would lead to global cost reductions of 20%. For New York City, USA, Hu et al [18] state a need for more public chargers that would allow electrifying more than half of the taxi fleet with BEV. Deyang et al [19] use simulation to determine techno-economically optimal battery sizes for electric taxis based on taxi data from Shanghai, China.…”
Section: A Existing Literature and Scope Of This Studymentioning
confidence: 99%
“…Several studies have shown that the operations of an e-taxi fleet are highly dependent on the availability of quick charging infrastructure. As a result, there are several studies that try to optimize the location of charging stations (e.g., [17,[25][26][27][28][29]).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Asamer et al ( 27 ) concluded that only 30 charging stations were needed to cover over 90% of the 800 e-taxis in Vienna but they do not account for the cost of queue delay for their charging stations. Hu et al required having over 650 charging stations to adequately support 50% fleet adoption of e-taxis in New York City ( 29 ). They ignore trip chaining behavior of taxis and assume that taxis continue along the trajectories observed from the data, recharging whenever they are within 1 mi of a charging station with state of charge (SOC) below 50%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The buffer zone is estimated by specifying a buffer distance around a parking lot. The buffer distance-also called the air distance-was used before in parking models such as [25], and optimizing charging stations for taxis in [26]. In our model, the buildings within the buffer distance are considered to be visited by the drivers parking in this specific parking lot.…”
Section: Stations Clusteringmentioning
confidence: 99%